Platelet lysates-based hydrogels as 3D cell culture platforms for cardiac regeneration - Lima, André Filipe Dias (2023)
Cardiovascular diseases are the leading cause of death in the world with myocardial infarction leading to heart failure and death of the victims. Since the current treatments do not restore the function of the cardiac tissue, tissue engineering aims to create cardiac patches to promote a better cardiac regeneration. In this study, two approaches of acellular and cellular strategies were chosen to produce cardiac patches for cardiac regeneration. On the acellular approach, platelet lysates modified with methacrylic groups (PLMA) were used to fabricate rehydrated scaffolds formed by freeze drying and were evaluated for cardiac patch application and to observe the impact of the freeze drying process on the hydrogel properties. The mechanical properties of the hydrogels increase with the freeze drying, not only in terms of Young’s modulus, ultimate stress and ultimate strain, but also in durability. Although the top surface porosity wasn’t different for all the PLMA concentrations used, PLMA scaffolds showed a high swelling ration, that decreases due to the liberation of protein from the scaffold matrix, a conductivity preliminary value on the same order of magnate of the human heart and capacity for being transported in a catheter. To evaluate this scaffold as a 3D culture platform, a successfully HUVECs assay was performed with the best performing PLMA concentration of 15%, showing, together with the physical properties results, promising results towards the use of this rehydrated hydrogels as cardiac patches for myocardial infarction regeneration. For the cellular approach, the idea was to build a system that could produce PLMA hydrogels incorporated with cardiomyocyte’s spheroids in a square feature and using size-controlled wells. To optimize this system, MG-63 cells were used since they can easily form spheroids. For a more physical characterization, PLMA hydrogels were also evaluated for important properties for biomedical application and for the cardiac tissue more specific. Mechanical properties of the hydrogels showed the increases in the elasticity modulus when increasing the PLMA concentration present in the hydrogels and water content tests demonstrated that all used PLMA concentration hydrogels had a high content of water. Using MG-63 cells, after 7 days the system had formed a few spheroids although the system did not work properly. The obtained results showed that PLMA hydrogels have good characteristics for biomedical and cardiac application and that the optimizing of this system might be able to form cardiomyocyte’s spheroids. In conclusion, the current results suggest these approaches can act as cardiac patches due to their hydrogel characteristics and cellular compatibility for this end, besides more interesting results can be obtained to support this outcome.